Basic science for sustainable development - Bandov, Goran (knjige, 2023)
Our common purpose in these proceedings is to address the most pressing contemporary challenges and search for innovative solutions so that the present imminent dangers of the destruction of human civilisation are overcome. New roads to our common bright future are opened. These contributions may also serve as guidelines on the road ahead and an invitation to pursue the goals toward this bright future and take the path toward the sustainable knowledge society we all are creating together.
Keywords: Trajnostni razvoj; zborniki; Znanost